2005
DOI: 10.1177/0021955x05059036
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Shear Viscosity and Solubility of Polystyrene Melts Containing Various Blowing Agents

Abstract: This article presents measured data on shear viscosity and solubility of HCFC-142b and HFC-134a/ethanol blowing agent laden polystyrene melts at different temperatures. This study establishes the baseline for more novel and innovative blowing agent systems to replace HCFC-142b. The shear viscosity is measured using a helical barrel rheometer. Apparent solubility is determined by observing the onset of gas bubble presence or absence in a specially designed optical cell with sapphire windows using a microscope–C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The presence of gas inside the polymer can reduce its viscosity, thus allowing the processability of the polymer at lower temperatures and pressures. This is an advantage particularly for biodegradable polymers, which are thermally sensitive and have narrow processing windows .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of gas inside the polymer can reduce its viscosity, thus allowing the processability of the polymer at lower temperatures and pressures. This is an advantage particularly for biodegradable polymers, which are thermally sensitive and have narrow processing windows .…”
Section: Introductionmentioning
confidence: 99%
“…If a blowing agent is injected and dissolved into a polymer melt, a decrease of viscosity can be observed. 1,7,13,14,26,27 Gerhardt et al 6 applied Doolittle's 28 free volume theory to describe the viscosity reduction to be caused by an increase in free volume and therefore increased mobility of molecular segments. This lowered viscosity is accompanied by a reduction of the glass transition temperature (T g Þ, which has been observed to be in linear correlation to pressure increase.…”
Section: Rheology Of Blowing Agent Loaded Polymer Systemsmentioning
confidence: 99%
“…29 This allows processing at lower temperatures compared to the extrusion of pure polymer. Several studies explored blowing agent-induced viscosity reduction, 1,7,13,14,26,27 notably Gerhardt et al investigated PDMS with CO 2 and concluded that a higher mass fraction of blowing agent results in a lower viscosity, but does not result in a changed shear rate induced slope of the flow curve. 2 This allows for the application of viscoelastic scaling models and construction of a master curve.…”
Section: Rheology Of Blowing Agent Loaded Polymer Systemsmentioning
confidence: 99%
“…Furthermore, it was shown that the pressure coefficient of polystyrene does not depend on the degree of branching and not significantly on the tacticity, either [Pantani and Sorrentino (2005)]. Most previous works on the rheology of solutions of a polymer melt and a blowing agent were devoted to shear flows [Royer et al (2001), Choudhary et al (2005), ].…”
Section: Introductionmentioning
confidence: 99%